Nanomedicine in Neuroscience: An Application Towards the Treatment of Various Neurological Diseases - Mohammed, Vajagathali; Kalarani, Iyshwarya B.; Veerabathiran, Ramakrishnan (Current Nanomedicine, 2022)
The effectiveness, cell viability, and selective delivery of medications and diagnostic substances to target organs, tissues, and organs are typical concerns in the care and prognosis of many illnesses. Neurological diseases pose complex challenges, as cerebral targeting represents a yet unresolved challenge in pharmacotherapy, owing to the blood-brain boundary, a densely compacted membrane of endothelial cells that prohibits undesired chemicals from reaching the brain. Engineered nanoparticles, with dimensions ranging from 1 to 100 nm, provide intriguing biomedical techniques that may allow for resolving these issues, including the ability to cross the bloodbrain barrier. It has substantially explored nanoparticles in the previous century, contributing to substantial progress in biomedical studies and medical procedures. Using many synthesized nanoparticles on the molecular level has given many potential gains in various domains of regenerative medicine, such as illness detection, cascaded cell treatment, tissue regeneration, medication, and gene editing. This review will encapsulate the novel developments of nanostructured components used in neurological diseases with an emphasis on the most recent discoveries and forecasts for the future of varied biological nanoparticles for tissue repair, drug inventions, and the synthesizing of the delivery mechanism.
Keywords: drug discovery